Sustainable development of the company on the basis of soft total quality management - Yuliia Prus (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2023)
The article is concerned with studying the impact of soft components of total quality management (TQM) on the company’s environmental and social sustainability. The subject of the research is a set of theoretical, methodical and practical recommendations for implementing the concept of total quality management to ensure sustainable development of a company. The purpose of the article is to theoretically substantiate and develop practical recommendations for identifying the impact of soft TQM on the sustainable development of a company. Achievement of this goal is ensured by fulfilling the following interrelated tasks: to summarise the existing soft TQM practices in the research of scientists, to allocate the features of soft TQM functioning in Ukrainian companies and their success in achieving environmental and social sustainability, to develop recommendations for improving the level of environmental and social sustainability of companies through the implementation of soft TQM practices. The research used general scientific and special methods of cognition: structural-logical, systemic and process approaches, the method of generalisation and comparison, questionnaires, methods of correlation and regression analysis, logical method, method of tabular presentation of data, scientific generalisation. The following results have been obtained: having analysed the work of scientists on the research’s subject, the work of the European Foundation for Quality Management, the aspects of TQM that cover the company’s business activities, as well as the problems that are specific to each of them, have been identified. To identify the level of implementation of detailed issues, a questionnaire was developed and completed by the heads of 68 Ukrainian companies between November 2022 and March 2023. It included a Likert scale assessment of each of the soft TQM dimensions (business management system, HR practices, continuously evolving processes, leading procurement procedures, stakeholder identification, and product competitiveness) based on 28 statements. Five hypotheses were proposed based on the literature on the research topic and our own analytical developments. The data obtained in the course of the survey were analysed using correlation and regression analyses. The results show that two practices – business management systems and human resource management practices – are related to environmental sustainability, while only the business management system is related to social sustainability. The article provides recommendations for supporting the sustainable development of the company. Conclusions. The study demonstrates the effectiveness of TQM practices in ensuring the sustainability of a company’s activities. The business management system affects both environmental and social sustainability of the company. Human resource management practices have a positive impact on environmental sustainability, but not on social sustainability, i.e. organisational factors are key to achieving environmental sustainability. Raising awareness of sustainability is the best way to promote the implementation of procedures that contribute to sustainability. Other TQM practices, such as continuously evolving processes, leading procurement procedures, stakeholder identification, and competitive products, do not affect a company’s environmental and social sustainability. The article raises topics for future research: why human resource management practices and continuously evolving processes do not affect sustainability. It is appropriate to deepen the case studies to identify the mechanisms by which TQM practices contribute to both environmental and social sustainability.